2015
DOI: 10.2196/jmir.4387
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and HIV: A Systematic Review of Uses of Social Media in HIV Communication

Abstract: BackgroundSocial media, including mobile technologies and social networking sites, are being used increasingly as part of human immunodeficiency virus (HIV) prevention and treatment efforts. As an important avenue for communication about HIV, social media use may continue to increase and become more widespread.ObjectiveThe objective of this paper is to present a comprehensive systematic review of the current published literature on the design, users, benefits, and limitations of using social media to communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
143
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 82 publications
(420 reference statements)
14
143
2
9
Order By: Relevance
“…The stigma associated with the disease often excludes PLHA from seeking voluntary counseling and testing services, and accessing the highly effective antiviral drugs that exist [710,17]. A growing number of studies in the past decade have addressed the issue of HIV/AIDS-related stigma [1820].…”
Section: Introductionmentioning
confidence: 99%
“…The stigma associated with the disease often excludes PLHA from seeking voluntary counseling and testing services, and accessing the highly effective antiviral drugs that exist [710,17]. A growing number of studies in the past decade have addressed the issue of HIV/AIDS-related stigma [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of social media, there has been burgeoning literature on its use in HIV and AIDS communication (Sanghee and Soojung, 2014;Taggart et al, 2015). Several studies on this regards have been carried out on the usefulness this new media in advancing health campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on this regards have been carried out on the usefulness this new media in advancing health campaign. Several studies have been carried out on the use of social media on HIV and AIDS prevention and intervention Taggart et al, 2015). Studies have also been carried out to assess use of social media for health purpose by college students (Sanghee and Soojung, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Horvath et al [10] and Taggart et al [11] showed that information sharing and socializing with others were the criteria most often cited when HIV patients describe an ideal online social network. Wang et al [12] modeled the discussions and interests of users of a forum for pregnant women using a topic model and showed that the women were sharing their experiences, fears and concerns about medications.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In the article by Horvath et al [10] the results of an online survey for HIV patients showed that 52% of the participants were considered non-compliant. The meta-analysis published by Taggart et al [11] identified two studies on HIV populations that demonstrated a link between the use of social media and the improvement of compliance to treatment among users. Moreover, Mao et al [14] showed that breast cancer patients offer practical strategies to deal with drug side effects and provide support to each other.…”
Section: Introduction Backgroundmentioning
confidence: 99%